The Effect Of Resistance Band Training Using The Set System Method On The Speed Of Teenage Pugilists' Sickle Kicks - Fitriyani, Dina; Sagitarius, Sagitarius; Mustaqim, Ridha; Mulyana, Mulyana (Journal Coaching Education Sports, 2024)
In various pencak silat matches it is often found that athletes lack good sickle kick speed as a result of attacks that use elements of speed, explosive power, endurance that are carried out repeatedly become less patterned and have no effect on opponents. The purpose of this study was to determine whether there is a significant effect of resistance band training using the set system method on the speed of adolescent pugilists' sickle kicks. The method in this study is a quantitative descriptive experimental method using a pretest-posttest control group design. The population in this study were 19 students and extracurricular students of SMKN 12 BANDUNG, and the sample was 14, the sampling technique used was purposive sampling. Instruments used peching, whistles, cameras, and Kinovea software. The results showed that resistance band training using the set system method had a significant effect on the speed of adolescent pugilists' sickle kicks. It can be concluded that speed training with a clear and routine training programme can increase sickle kick speed.